OPTIMIZATION OF QUR'ANIC STUDIES PROGRAM THROUGH CIPP EVALUATION: A Case Study at Ma'had Al-Jami'ah IAIN Fattahul Muluk Papua - Kahfi, Sahibul; Rokhmah, Siti; Muhyidin, Syaiful; Taslim, Muhammad; Zulihi, Zulihi (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: This study was motivated by the implementation of the Qur'an study program in ma'had which was not optimal, due to limited human resources, budget, and low involvement of mahasantri. Objective: This study aims to evaluate the implementation of the program and formulate strategies to optimize the al-Qur'an study program in Ma'had. Methods: This research uses a qualitative method of evaluative approach, with data collection techniques in the form of interviews, observation, and documentation and data analysis using the Miles and Huberman model. Results: Context evaluation of program implementation is quite in line with the vision, mission, and goals of the ma'had while the program needs analysis component has not been carried out comprehensively. 2. Input evaluation in general, the infrastructure component is quite good, while the curriculum component is not yet standardized, the teaching staff is limited and the budget is not adequate. 3. Process evaluation shows that the implementation of the program generally runs quite well. However, the involvement of mahasantri is very low, the learning method is still monotonous, and there are several obstacles such as limited teaching staff, limited time, and low motivation of mahasantri. 4. Product evaluation shows results that are not yet optimal. The number of mahasantri who passed the BTA certification was still very low. Even so, there is an increase in the ability of mahasantri to read the Qur'an and an increase in academic achievement based on the value of the BTA course. Conclusion: The implementation of the al-Qur'an study program in ma'had still faces various obstacles in the aspects of context, input, process, and product so that the results achieved are not optimal. Therefore, an optimization strategy is needed through strengthening the curriculum, improving the quality and quantity of teaching staff, providing adequate infrastructure, and sufficient budget support so that the program can run more effectively and sustainably. By optimizing this strategy, Ma'had is expected to be able to improve the quality of al-Qur'an study program in Ma'had.